Transresonant Evolution of Spherical Waves Governed by the Perturbed Wave Equation - Bhattacharyya, D.; Galiev, Sh.U.; Panova, O.P. (Проблемы прочности, 2002)
An equation of nonlinear acoustics for radial
spherical waves in a solid body has been derived.
An approximate solution to this equation
is presented, which takes into account nonlinear,
spatial, and dissipative effects. It is found
that in the transresonant frequency band nonlinear
spherical waves may be excited, which it is
difficult to classify as the well-known solitonor
cnoidal- or shock- or breather-type waves.
These resonant spherical waves are also quite
different from the well-known sawtooth spherical
waves. However, some expressions for the
spherical waves resemble the solutions for surface
waves. Выводится уравнение нелинейной акустики для радиальных сферических волн в твердом
теле. Приближенное решение этого уравнения учитывает нелинейные, пространственные и
диссипативные эффекты. Установлено, что в трансрезонансной частотной полосе могут
возбуждаться нелинейные сферические волны, которые трудно классифицировать как хорошо
известные солитон-, кноидал-, ударные или бриз-тип волны. Эти резонансные сферические
волны также существенно отличаются от хорошо известных гладких сферических
волн. Однако некоторые выражения для сферических волн напоминают известные решения
для поверхностных волн. Виводиться рівняння нелінійної акустики для сферичних хвиль у твердому
тілі. Наближений розв’язок цього рівняння ураховує нелінійні, просторові і
дисипативні ефекти. Установлено, що у трансрезонансній смузі частот можуть
збуджуватися нелінійні сферичні хвилі, які важко класифікувати як
добре відомі солитон-, кноїдал-, ударні або бриз-тип хвилі. Ці резонансні
сферичні хвилі також суттєво відрізняються від добре відомих гладких
сферичних хвиль. Однак деякі вирази для сферичних хвиль нагадують
відомі розв’язки для поверхневих хвиль.